Interventions in sports settings to reduce risky alcohol consumption and alcohol-related harm: a systematic review. Issue 1 (December 2016) - Kingsland, Melanie; Wiggers, John; Vashum, Khanrin; Hodder, Rebecca; Wolfenden, Luke
Abstract Background Elevated levels of risky alcohol consumption and alcohol-related harm have been reported for sportspeople and supporters compared to non-sporting populations. Limited systematic reviews have been conducted to assess the effect of interventions targeting such behaviours. Methods A review was undertaken to determine if interventions implemented in sports settings decreased alcohol consumption and related harms. Studies were included that implemented interventions within sports settings; measured alcohol consumption or alcohol-related injury or violence and were either randomised controlled trials, staggered enrolment trials, stepped-wedged trials, quasi-randomised trials, quasi-experimental trials or natural experiments. Studies without a parallel comparison group were excluded. Studies from both published and grey literature were included. Two authors independently screened potential studies against the eligibility criteria, and two authors independently extracted data from included studies and assessed risk of bias. The results of included studies were synthesised narratively. Results The title and abstract of 6382 papers and the full text of 45 of these papers were screened for eligibility. Three studies met the inclusion criteria for the review. One of the included studies was a randomised controlled trial (RCT) of a cognitive-behavioural intervention with athletes within an Olympic training facility in the USA. The study reported a significant change in alcohol use between pre-test and follow-up between intervention and control groups. The other two studies were RCTs in community sports clubs in Ireland and Australia. The Australian study found a significant intervention effect for both risky alcohol consumption at sports clubs and overall risk of alcohol-related harm. The Irish study found no significant intervention effect. Conclusions A limited number of studies have been conducted to assess the effect of interventions implemented in sports settings on alcohol consumption and related harms. While two of the three studies found significant intervention effects, it is difficult to determine the extent to which such effects are generalisable. Further controlled trials are required in this setting. Systematic review registration PROSPEROCRD42014001739